Associations between laboratory-based performance indicators and on-snow competitive success in elite cross-country skiing: A 15-year analysis of the Swiss National Team - Bucher, E.; Wehrlin, J. P.; Trösch, S.; Millet, G. P.; Steiner, T. (International Journal of Sports Physiology and Performance, 2026)
Purpose: This study examined the associations between laboratory-based performance indicators and competitive success in elite cross-country skiing, considering sex- and age-related differences over a 15-year period.